Practical cryptography: algorithms and implementations using C++ - Azad, Saiful (CRC Press, Taylor & Francis Group, USA, 2014)
Many books are available on the subject of cryptography. Most of these books focus on only the theoretical aspects of cryptography. Some books that include cryptographic algorithms with practical programming codes are by this time (i.e., at the preparation of this book) outdated. Though cryptography is a classical subject in which often "old is gold," many new techniques and algorithms have been developed in recent years. These are the main points that motivated us to write and edit this book.